Iron-catalyzed clean dehydrogenative coupling of alcohols with P(O)–H compounds: a new protocol for ROH phosphorylation. Issue 38 (1st September 2016) - Li, Chunya; Chen, Tieqiao; Han, Li-Biao
Abstract : An efficient oxygen–phosphoryl bond-forming reaction via iron-catalyzed cross dehydrogenative coupling has been developed. The reaction proceeds efficiently under oxidant- and halide-free conditions with H2 liberation, and represents a straightforward method to prepare organophosphoryl compounds from alcohols and P(O)–H compounds. Abstract : An efficient oxygen–phosphoryl bond-forming reaction via iron-catalyzed cross dehydrogenative coupling has been developed. This transformation proceeds efficiently under oxidant- and halide-free reaction conditions with H2 liberation, and represents a straightforward method to prepare valuable organophosphoryl compounds from the readily available alcohols and P(O)–H compounds.